2018
DOI: 10.3346/jkms.2018.33.e150
|View full text |Cite
|
Sign up to set email alerts
|

Association between BMI for Obesity and Distress about Appearance in Korean Adolescents

Abstract: BackgroundPrevious research has related obesity to body dissatisfaction and low self-esteem. This study aimed to evaluate this relation between obesity and distress about appearance.MethodsWe performed a cross-sectional study using data from the Korea Youth Risk Behavior Web-based Survey for 288,390 participants assessed from 2009 to 2012. The participants were categorized according to body mass index; obese, overweight, healthy weight, and underweight. The relation between obesity and distress was analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that a high tendency towards appearance comparison was associated with eating disorders [46]. According to a Korean study, females may exert greater pressure on their appearance [47]. When they believe that their body does not meet social or cultural standards, they may try to change their body image by fasting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that a high tendency towards appearance comparison was associated with eating disorders [46]. According to a Korean study, females may exert greater pressure on their appearance [47]. When they believe that their body does not meet social or cultural standards, they may try to change their body image by fasting.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been consistently linked to various negative health outcomes, such as obesity‐related cancers, osteoarthritis, type 2 diabetes, cardiovascular diseases, psychological disturbances and poor mental health in adults 4–6 . Moreover, children and adolescents with obesity often face challenges related to their appearance, 7 weight stigma, 8 and becoming victims of bullying 9 because of their large body size. Consequently, these experiences could render them vulnerable to the development of mental health disorders such as anxiety and suicide attempts, 10 sleep problems and lower academic performance 11 …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, another study from the same group linked low birth weight to increased mortality from cardiovascular disease in men [ 2 ]. Since then there has been an accumulating body of evidence that offspring metabolism and body composition are prenatally programmed in utero [ 3 6 ]. Indeed, maternal diet manipulation, present before and/or during the perinatal period, represents an important form of in utero stress and may program offspring’s metabolism regardless of maternal genetics [ 1 , 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%